Selected Milestones in Antiviral Drug Development - Erik De Clercq (Viruses, 2024)
This review article will describe the (wide) variety of approaches that I envisaged to develop a specific therapy for viral infections: (i) interferon and its inducers, (ii) HSV, VZV and CMV inhibitors, (iii) NRTIs (nucleoside reverse transcriptase inhibitors), NtRTIs (nucleotide reverse transcriptase inhibitors) and NNRTIs (non-nucleoside reverse transcriptase inhibitors) as HIV inhibitors, (iv) NtRTIs as HBV inhibitors, and finally, (v) the transition of an HIV inhibitor to a stem cell mobilizer, as exemplified by AMD-3100 (Mozobil®).